Integrated metabolome and transcriptome analysis reveals potential mechanism during the bud dormancy transition of Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) Hsiao - Guan, Huan; Zhao, Yuhuan; Chen, Qing; Zhang, Qianqian; Yang, Pengpeng; Sun, Shuying; Chen, Guilin (Frontiers in Plant Science, 2025)
Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) Hsiao (AMM) is an important medicinal plant that is used for both medicine and food. It is widely used in Asia and South Asia. It is normally cultivated by transplanting the annual rhizomes. Understanding the dormancy of underground buds of AMM is essential for its harvest and transplantation. Despite thorough research on bud dormancy in perennial woody plants, perennial herbs, and especially medicinal plants, such as AMM, have rarely been studied. We analyzed the transcriptome and non-targeted metabolome of dormant buds stage-by-stage to investigate the regulatory mechanism of the transition from endo- to ecodormancy. A total of 1,069 differentially accumulated metabolites (DAMs) participated in amino acid and carbohydrate metabolism. Transcriptome analysis revealed 16,832 differentially expressed genes (DEGs). Functional enrichment analysis indicated that carbohydrate metabolism, hormone signaling pathways, and amino acid metabolism contributed to the transition from endo- to ecodormancy. Starch and sucrose metabolism and hormone signaling pathways were mainly analyzed in the transition between different dormancy states. During the transition from endo- to ecodormancy, the highest content of indole-3-acetic acid (IAA) and the highest number of DEGs enriched in the IAA signaling pathway demonstrated that IAA may play a key role in this process. We obtained candidate genes through co-expression network analysis, such as BGL, GN, glgC, and glgB, which are involved in starch and sucrose metabolism. The transcription factors MYB, ERF, bHLH, zinc finger, and MADS-box may regulate the genes involved in hormone signal transduction and starch and sucrose metabolism, which are critical for regulating the transition from endo- to ecodormancy in AMM buds. In summary, these results provide insights into the novel regulatory mechanism of the transition of endo- to ecodormancy in underground buds of AMM and offer new analytical strategies for breaking dormancy in advance and shortening breeding time.